Bilateral Mechanically-Assisted Crevice Corrosion Resulting in Femoral Stem-Head Dissociation in Metal-on-Polyethylene Total Hip Arthroplasty - McAleese, Timothy (Arthroplast Today, 2021)
There are emerging reports of complications related to corrosion in modular femoral components. We report a unique case describing an 83-year-old man with bilateral mechanically-assisted crevice corrosion in hip replacements performed 10 years previously, by the same surgeon using the same size 3 Accolade TMZF stem and same 44-mm CoCr LFIT V40 head (Stryker Orthopedics, Mahwah NJ). Our patient presented with complete femoral stem-head complex dissociation of his right hip and elevated serum cobalt and chromium levels. He subsequently underwent right hip revision arthroplasty while his contralateral hip is monitored closely as an outpatient. This case helps to define the poorly understood mechanisms and component design factors implicated in this emerging issue. We also hope to provoke discussions about guidelines for monitoring and revising failing metal-on-polyethylene arthroplasty systems.